A review on gut microbiota and migraine severity: a complex relationship - Noha M. Gamil; Rana M. Ghorab; Reham Z. Elsadawy; Nada M. Khadrawy; Mohamed Abdelhamid; Khalid A. Ismael; Omar A. Mohamed; Mohamed M. Ata; Habiba T. Jalal; Joumana E. Zeidan; Reem T. Rashed; Riham A. El-Shiekh (Inflammopharmacology, 2026)
The gut-brain axis plays a vital role in migraine pathophysiology. Studies highlight reciprocal interactions between the central nervous system and the gastrointestinal tract. Previous research suggests that factors such as gut microbiota profiles, inflammatory mediators, neuropeptides, serotonin pathways, stress hormones, and nutritional substances influence this interaction. The pathophysiology of migraine has been linked to changes in the gut-brain axis, which affects migraine severity and frequency. Additionally, dietary approaches, including the ketogenic diet, vitamin D supplementation, omega-3 intake, probiotics, and weight loss plans, have shown promising effects in reducing migraine symptoms by positively impacting the gut microbiota and the gut-brain axis. Understanding these connections could lead to novel therapeutic strategies for effectively managing migraines. It is worth noting that research highlights several innovative treatments for migraine, such as Zelirex and Cevimide, implantable devices like Cefaly and Revilion, and new effective routes of administration for Sumatriptan. Finally, patients’ perspectives and concerns were thoroughly discussed, with a focus on future directions in the migraine-gut axis research.

Cytoprotective effect of garlic alone versus co-administration of garlic and resveratrol in adriamycin-induced lung toxicity in albino rat: light microscopic, ultrastructural and immunohistochemical study - Noha A. Rashed; Omnia I. Ismail (Journal of Molecular Histology, 2024)

Ameliorative Effects of Zinc Oxide, in Either Conventional or Nanoformulation, Against Bisphenol A Toxicity on Reproductive Performance, Oxidative Status, Gene Expression and Histopathology in Adult Male Rats - Dina M. M. H. El-Kossi; Shawky S. Ibrahim; Kamel M. A. Hassanin; Nashwa Hamad; Noha A. Rashed; Ahmed Abdel-Wahab (Biological Trace Element Research, 2024)
Bisphenol A (BPA) is a widely used endocrine disruptor that represents a significant risk to male reproductive function. Zinc (Zn) is vital for appropriate development of testes and to guarantee optimal testicular function and spermatogenesis. Our goal was to investigate if zinc oxide (ZnO), either in conventional or nanoformulation, could safeguard adult male rats’ reproductive performance against the damaging effects of BPA. Signaling expression of CYP11A1 and Nrf-2 in the testis, testicular oxidant-antioxidant status, Bax/Bcl-2 apoptotic ratio, and histological examination of various reproductive organs were all evaluated. Twenty-eight adult male albino rats were divided randomly into 4 groups (7 animals each) including the control, BPA, conventional zinc oxide (cZnO) + BPA, and zinc oxide nanoparticles (ZnO-NPs) + BPA groups. The study was extended for 2 successive months. Our findings revealed strong negative effects of BPA on sperm cell characteristics such as sperm motility, viability, concentration and abnormalities. Additionally, BPA reduced serum levels of testosterone, triiodothyronine (T3), and thyroxine (T4). Also, it evoked marked oxidative stress in the testes; elevating malondialdehyde (MDA) and reducing total antioxidant capacity (TAC). BPA significantly downregulated testicular mRNA relative expression levels of CYP11A1 and Nrf-2 , compared to control. Testicular apoptosis was also prompted by increasing Bax/ Bcl-2 ratio in testicular tissue. Histopathological findings in the testes, epididymis, prostate gland, and seminal vesicle confirmed the detrimental effects of BPA. Interestingly, cZnO and ZnO-NPs significantly alleviated all negative effects of BPA, but ZnO-NPs performed better. In conclusion, our findings point to ZnO, specifically ZnO-NPs, as a viable treatment for BPA-induced testicular dysfunction.